PENGARUH UKURAN PERUSAHAAN, UMUR PERUSAHAAN, UKURAN DEWAN KOMISARIS, PROFITABILITAS DAN LEVERAGE TERHADAP PENGUNGKAPAN TANGGUNG JAWAB SOSIAL P ERUSAHAAN (Studi Empiris Pada Perusahaan BUMN yang terdaftar di Bursa Efek Indonesia pada Tahun 2013-2015) - Windy Wulandari; Azwir Nasir Azwir Nasir; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was examined the influence of Firm Size, Firm Age, Independent Commisaries Board, Profitability And Leverageto CSR Disclosure. The population in this study are all BUMN Companies listed in Bursa Efek Indonesia in years 2013-2015. This research is included in quantitative research. The type of data used in this study is secondary data from financial statement of the aforementioned BUMN Companies and data derived from the IDX fact book and Indonesian Capital Market Directory, sampling is done by the method of purposive sampling is the technique of sampling with certain considerations. The total sample in this study are 17 firms. These data were analyzed using multiple regression analysis with SPSS Version 17. The results of this study showed that Firm Size affects CSR Disclosure with significant value 0,000, Firm Ageaffects CSR Disclosure with significant value 0,005, Independent Commisaries Boardaffects CSR Disclosure with significant value 0,035, Profitability affects CSR Disclosure with significant value 0,002 and Leverage affects CSR Disclosure with significant value 0,009. So the conclusion of this research is all hypothesis presented acceptable.Keywords : CSR Disclosure, Firm Size, Firm Age, Independent Commisaries Board, Profitability, Leverage